Diplomasi Publik : Bagaimana posisinya bagi Indonesia? - Sofia Trisni (Frequency of International Relations (FETRIAN), 2020)
Public diplomacy is a popular instrument used to meet the interests of the state. It claims that nowadays, nations are competed to pay attention to the implementation of public diplomacy. This article is interested in exploring the phenomenon above by research Indonesian public diplomacy to find out the position of public diplomacy for Indonesia. This article uses the literature study method concerning documents from the Ministry of Foreign Affairs website, several speeches by state officials, and journal articles. By referring to the concept of public diplomacy, the author tries to analyze the position of public diplomacy for Indonesia. The documents used as data sources in this paper indicate that public diplomacy has occupied a particular spot for Indonesia, bearing in mind that Indonesia already has a special directorate to take care of the implementation of public diplomacy. Additionally, some objectives of public diplomacy are often delivered by state officials in several of their speeches which, indicates its specialty.